Salivary Albumin and Alkaline Phosphatase in Infants: Exploring the Link Between Early Dental Development and Biomarkers - Nelwan, Sindy Cornelia; Tedjosasongko, Udijanto; Saskianti, Tania; Dewi, Ardianti Maartrina; Setyowati, Erika; Putri, Sofia Tandya; Nowwarote, Nunthawan (European Journal of Dentistry, 2025)
This study aims to investigate the relationship between dental age and the levels of albumin and alkaline phosphatase (ALP) in saliva among children aged 6 to 24 months. This study evaluates their potential as noninvasive biomarkers for monitoring dental development. Specifically, it sought to determine whether these salivary proteins increase proportionally with dental age, providing an objective method to assess tooth eruption patterns in early childhood.Ethical approval was granted by the Airlangga University Hospital ethics committee to conduct this cross-sectional study in 33 children aged 6 to 24 months to collect data on dental age, albumin, and ALP levels in saliva. Saliva was taken using an absorbent paper and tested by enzyme-linked immunosorbent assay.The data obtained were then analyzed by statistical tests using SPSS. Correlation test was analyzed using the Pearson's correlation test. A significance level of p < 0.05 was used to determine statistical significance.The correlation test showed a significant relationship between dental age, albumin, and ALP levels in saliva (p < 0.05), albumin and ALP levels in saliva increase along the children's dental age.This significant relationship suggests albumin and ALP in saliva as potential biomarkers in detecting dental age and tooth eruption in children.
Keywords: tooth eruption; dental age; albumin; alkaline phosphatase; saliva; good health and well-being